PERAN KOMUNITAS SAHABAT DIFABEL DALAM PEMENUHAN HAK KETENAGAKERJAAN PENYANDANG DIFABEL KOTA SEMARANG - Azmi Anti Mutiah; Puji Astuti (Journal of Politic and Government Studies, 2018)
This research has a goal to identify the role of Komunitas Sahabat Difabel as a Community-based Organization (CBO) in the fulfillment of employment rights of people with different abilities in Semarang District. How the difable community play its role so that it cann succeed in fighting for the rights of employment of people with different abilities (difable), and also explain the opportunities and obstacle faced by the community. The Difable’s Employments Rights are based on the Central Java Regulation on the Fulfillment of the Rights of Persons with Disabilities. The type of this research is descriptive through a qualitative approach. The source of data comes from primary data derived from the results of in-depth interviews of research informants and secondary data come from the archives and documentation activities. The technique of selecting informants using purposive sampling. The results of the study found that the roles that has been successfully executed are holding job training in cooperation with the government, giving information of a job vacancy and facilitator of recruitment of difable labors with companies, provide marketing facilities of difable products by forming Saung Happy Difabel SMEs, and accompanying labor recruitment process and consultant of the companies when there is a problem of difable labors with the company. Its opportunities are reputation and strategic location of the existing community in the city center in Central Java. While some of the obstacles are the behavior of the difable labors who often become industrial relations disputes, the work conditions incriminating the difable, and the stigma of the business against the ability of people with disabilities. The recommendations for Komunitas Sahabat Difabel are to improve the internal organization including defining tasks and authority within the organizational structure, optimizing empowerment and and creative marketing for Saung Happy Difabel SME, and improve the relationships with external sectors, such as government, private, and other community. Keywords : Komunitas Sahabat Difabel, difable rights, difable labor